EFFECTIVENESS OF COLLABORATIVE STRATEGIC TO IMPROVE READING COMPREHENSION OF STUDENTS AT SMP NEGERI 23 OKU: Teaching Reading Comprehension, Collaborative Strategic Reading - Yesi Novita Sari; Neti Lastri; Nurul Afifah; Nopa Yusnilita; Novarita Novarita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2023)
This research aims to determine students' reading comprehension in eighth grade students of SMP Negeri 23 OKU who are taught by using Collaborative Strategic Reading. this research is counducted by using pre-experimental research design. the population of this research were all students of class VIII SMP Negeri 23 OKU. the total population is 164 students, and 30 students were taken as the sample through claster random sempling. the pre-test and post-test were used as the techniques for collecting the data. base on the result of research findings the researchers found that the average pre-test score was 48,88 and the post-test score was to 74,00. from statistical analysis, research found that the value of sig.=0.000 les than the value of significance level a=0.05 this show that the alternative hypothesis was accepted. it can be conclude that collaborative strategic reading was effectiveness to improve reading comprehension of eighth grade students at SMP Negeri 23 OKU. by using collaborative strategic reading students are more active and participate in the teaching and learning process of reading comprehension. therefore, collaborative strategic reading can be an alternative strategy for teachers in teaching reading which can improve their reading comprehension skill.